Pengaruh Financial Leverage, Profitabilitas Dan Corporate Social Responsibility Terhadap Nilai Perusahaan - Kartiva, Kartiva; Wijaya, Trisnadi (MDP Student Conference, 2024)
This research aims to examine the effect of Financial Leverage, Profitability and Corporate Social Responsibility on firm value in JII70 companies listed on the IDX in 2020-2022. Sample collection using purposive sampling technique so as to get 26 sample companies. The data analysis technique uses multiple linear regression tests. The results showed that Financial Leverage, Profitability and and Corporate Social Responsibility had a partial effect on firm value.